Recombinant Production of MFHR1, A Novel Synthetic Multitarget Complement Inhibitor, in Moss Bioreactors - Top, Oguz; Parsons, Juliana; Bohlender, Lennard L.; Michelfelder, Stefan; Kopp, Phillipp; Busch-Steenberg, Christian; Hoernstein, Sebastian N. W.; Zipfel, Peter F.; Häffner, Karsten; Reski, Ralf; Decker, Eva L. (Frontiers in Plant Science, 2019)
The human complement system is an important part of the immune system responsible for lysis and elimination of invading microorganisms and apoptotic body cells. Improper activation of the system due to deficiency, mutations or autoantibodies of complement regulators, mainly factor H (FH) and FH-related proteins (FHR), causes severe kidney and eye diseases. However, there is no recombinant FH therapeutic available on the market. The first successful recombinant production of FH was accomplished with the moss bioreactor, Physcomitrella patens. Recently, a synthetic regulator, MFHR1, was designed to generate a multitarget complement inhibitor that combines the activities of FH and the FH-related protein 1 (FHR1). The potential of MFHR1 was demonstrated in a proof-of-concept study with transiently transfected insect cells. Here, we present the stable production of recombinant glyco-engineered MFHR1 in the moss bioreactor. The key features of this system are precise genome engineering via homologous recombination, Good Manufacturing Practice-compliant production in photobioreactors, high batch-to-batch reproducibility and product stability. Several potential biopharmaceuticals are being produced in this system. In some cases, these are even biobetters, i.e. the recombinant proteins produced in moss have a superior quality compared to their counterparts from mammalian systems as for example moss-made aGal, which successfully passed phase I clinical trials. Via mass spectrometry-based structural analysis of moss-produced MFHR1 we now prove the correct synthesis and modification of this glycoprotein with predominantly complex-type N-glycan attachment. Moss-produced MFHR1 exhibits cofactor and decay acceleration activities comparable to FH, and its mechanism of action on multiple levels within the alternative pathway of complement activation led to a strong inhibitory activity on the whole alternative pathway, which was higher than the physiological regulator FH.